An approach to revising mHealth interventions for children and families: A case example in sickle cell disease. Issue 6 (8th August 2019) - Phillips, Shannon; Kanter, Julie; Ruggiero, Kenneth J.; Mueller, Martina; Johnson, Mary A.; Kelechi, Teresa J.
Abstract: Frameworks for developing mHealth interventions that are informed by the end‐user and improve accessibility are necessary to ensure interventions meet the needs of the intended population and advance the science of health behavior change. The approach described in this paper addresses a gap in the mHealth development literature by describing a step‐by‐step method for evaluating and revising the mHealth interventions for health behavior change in child–parent dyads. Furthermore, this approach introduces the Website Analysis and MeasureMent Inventory framework as an initial coding structure for analyzing qualitative data to gauge appeal and enhance engagement of intervention for end‐users. This method uses specific considerations for child–parent dyads and details an example in the development and refinement of a mobile application for self‐management in children with sickle cell disease. This approach is translatable to populations of children with other chronic conditions and to other health behaviors.